An impedance based method for acoustical absorption coefficient measurement and membrane health monitoring - Xie, Jin (2010)
Impedance, as one of frequency response functions, characterizes the dynamic behavior of the system and does not change with external excitations. Mechanical impedance is useful for applications such as modal testing, mechanical design and vibration monitoring, while acoustical impedance is closely related with the characterization of sound absorption material. However, measurement methods of acoustical/mechanical impedance are not as developed as for their theoretical counterparts due to lack of appropriate transducers to measure excitation or response variables. In this thesis, based on the simultaneous sensing and actuating (SSA) capability of a dynamic microphone, the absorption coefficient of acoustical materials is measured and the state of health of a membrane is monitored at the end of a tube. In addition, a similar SSA technique is studied for a micro PZT cantilever transducer to measure mechanical impedance of micro structures. The SSA capability of a dynamic microphone is firstly studied. With the calibrated transduction matrix, the dynamic microphone could perform well as a simultaneous sensor and actuator, which is validated by the measurement of mechanical impedance of point masses.